Epstein Barr virus induced pneumonitis: a rare entity in immunocompetent baby - Singh, Vineet K.; Verma, Manisha; Kumar, Yarraguntla K.; Bhargav, Mithlesh (International Journal of Research in Medical Sciences, 2023)
Acute infectious interstitial pneumonitis (IP) (Epstein Barr virus (EBV)-associated IP) in children has been most commonly associated with human immunodeficiency virus (HIV) infection and immunocompromised hosts. Here we report a case of EBV-associated interstitial pneumonitis with cervical lymphadenopathy in an immunocompetent child. Patient underwent extensive routine and serologic workup which revealed positive polymerase chain reaction (PCR) for EBV, pointing towards the diagnosis of EBV induced pneumonitis. It is a very rare entity and is hardly seen among immunocompetent individuals especially young children. The aim of this case report is to bring to our notice that among all described pneumonias, EBV induced pneumonitis can be a possibility while dealing with lung infections.